Transformation of Population Administration Services: Technology-Based Development of the Klampid New Generation (KNG) Application in Pegirian Village, Surabaya City - Basuki, Raka Adhitya Dwiky Ferliansyah (LifeSciFi, 2024)
The Klampid New Generation (KNG) platform, which consists of an application and an official website, is an initiative of the Surabaya City Population and Civil Registry Service which aims to simplify the online population administration process. This platform facilitates various public service and civil registration tasks, including legal document verification, updating population data, civil registration processes and population registration tasks. This service is important for documenting important life events that require updates or changes to family cards, identity documents, and addresses or residence status. This approach offers a comprehensive assessment of how well the KNG platform meets its intended objectives and its impact on community and population administration processes. The effectiveness of the e-Klampid program has not been achieved optimally. Of the five effectiveness indicators assessed, only one indicator, namely punctuality, was considered effective. Meanwhile, the other four indicators show a low level of effectiveness. Indicators of program understanding were found to be ineffective due to a lack of public understanding of the implementation of KNG.